2002
DOI: 10.1074/jbc.m202223200
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Regulation of LFA-1 Activation and Neutrophil Arrest on Intercellular Adhesion Molecule 1 (ICAM-1) in Shear Flow

Abstract: Neutrophil recruitment during acute inflammation is triggered by G-protein-linked chemotactic receptors that in turn activate ␤ 2 integrin (CD18), deemed a critical step in facilitating cell capture and arrest under the shear force of blood flow. A conformational switch in the I domain allosteric site (IDAS) and in CD18 regulates LFA-1 affinity for endothelial ligands including intercellular adhesion molecule 1 (ICAM-1). We examined the dynamics of CD18 activation in terms of the efficiency of neutrophil captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 48 publications
(60 reference statements)
5
122
0
1
Order By: Relevance
“…Recently, we reported that neutrophil arrest on the endothelial ligand ICAM-1 is tightly controlled by IL-8 receptor occupancy and CD18 activation [18]. Adhesion was triggered by stimulating neutrophils with a threshold concentration of IL-8 ($0.1 nM) and increased 4-fold up to maximal adhesion at 1 nM of stimulation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that neutrophil arrest on the endothelial ligand ICAM-1 is tightly controlled by IL-8 receptor occupancy and CD18 activation [18]. Adhesion was triggered by stimulating neutrophils with a threshold concentration of IL-8 ($0.1 nM) and increased 4-fold up to maximal adhesion at 1 nM of stimulation [18].…”
Section: Introductionmentioning
confidence: 99%
“…CD11a (integrin alpha L, or Itgal ) heterodimerizes with the β2‐integrin CD18 to form LFA1. LFA1 interacts with ICAM‐1 and has roles in transendothelial migration, activation, and differentiation of lymphocytes 15, 16, 17, 18. We found that while CD11a is expressed on nearly all hematopoietic lineages, it is downregulated on HSCs 19.…”
Section: Introductionmentioning
confidence: 74%
“…This weakening of adhesion strength correlates with a reversibility in high affinity b2 integrin as reported for neutrophils exposed to soluble IL-8 over the same timecourse. 29 In contrast, exposure to a concentration of 0.01 nM or lower IL-8 had no detectable impact on neutrophil arrest efficiency over the course of 3 min. Neutrophil arrest to an L-E monolayer is dependent on the activation of the b2-integrin Mac-1, which is rapidly upregulated on the plasma membrane upon neutrophil activation.…”
Section: Dynamics Of Neutrophil Deceleration Within Microfluidicsmentioning
confidence: 92%
“…Based on our previously reported relation between chemokine concentration and integrin activation, we estimate that as few as 15 000 active b2 integrins on the surface of a neutrophil are capable of effecting arrest. 29 The reversibility of adhesion strength following chemokine exposure reveals that neutrophil recruitment from the circulation requires precise cooperation between chemotactic signal and the ligation and activation of integrins.…”
Section: Discussionmentioning
confidence: 99%